GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS PERINDUSTRIAN DAN PERDAGANGAN PROVINSI BANTEN - Permana, Angrian; Puspa, Rani; Fauzi, Muhdar (Bhinneka Multidisiplin Journal, 2024)
The purpose of this research were to determine leadership style on official performance, work discipline on official performance, and leadrship style and work discipline simultaneously on officials performance. This research used a quantitatve method with regression analysis tool. The population and samples were 88 officials using SPSS tool. The result were leadership style has positif and significant influence on official performance, work discipline has positive and significant influence on official performance, and leadership style and work discipline simultaneously has positive and significant influence  on official performance